The Pengaruh mobilisasi dini terhadap penyembuhan luka post operasi sectio cesarea - Marmawira Hamzah; Widia Shofa Ilmiah (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Early mobilization is a non-pharmacological intervention believed to accelerate the healing process of postoperative wounds, including in patients who have undergone cesarean section. In Indonesia, the estimated proportion of cesarean section deliveries ranges from 30% to 80% of total births. Purpose: To examine the impact of early mobilization on wound recovery in mothers after cesarean section surgery. Method: This study used a quantitative approach with a quasi-experimental design and was conducted from January to March 2025. A total of 30 participants were determined through purposive sampling based on specific criteria. Data collection was carried out through direct observation of wound conditions using clinical indicators, then analyzed using Kendall's Tau statistical test at a significance level of 0.05. Results: The analysis shows a significant correlation between early mobilization and accelerated wound healing after C-section. These findings reinforce that early mobilization can serve as an efficient and safe non-pharmacological intervention in supporting post-surgical recovery. Conclusion: Therefore, the active involvement of health workers in providing education and assistance to post-operative mothers is highly recommended so that mobilization can be optimally applied according to the clinical condition of each patient. Suggestion: Health workers, especially midwives and nurses in the postpartum care unit, are expected to play an active role in providing education, motivation, and assistance to mothers who have undergone C-sections so that they can mobilize early according to their physical condition.